2012
DOI: 10.1093/icvts/ivs405
|View full text |Cite
|
Sign up to set email alerts
|

No extensive experience in open procedures is needed to learn lobectomy by video-assisted thoracic surgery

Abstract: With thorough preparation of trainees and training on selected patients under close supervision, the learning curve can be overcome with good results even if the trainee has limited prior experience in open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…This indicates that VATS has not gained a widespread acceptance amongst surgeons. It could be due to a long learning curve, perceived longer operation time or lack of experience in management of intraoperative complications [10,18]. The fact that many studies are conducted at high-volume teaching hospitals may make surgeons at rural hospitals question the generalizability of these studies, and therefore hesitate to choose the VATS procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that VATS has not gained a widespread acceptance amongst surgeons. It could be due to a long learning curve, perceived longer operation time or lack of experience in management of intraoperative complications [10,18]. The fact that many studies are conducted at high-volume teaching hospitals may make surgeons at rural hospitals question the generalizability of these studies, and therefore hesitate to choose the VATS procedure.…”
Section: Discussionmentioning
confidence: 99%
“…There is a bulk of data describing and defining the learning curve of surgical trainees without significant experience with open lobectomy, starting to learn VATS lobectomy from scratch. Konge et al showed that the learning curve can be overcome with good results, even if the beginner surgeon has limited prior experience in open surgery (19).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, many studies have analysed the learning curve for different surgical techniques (12,(19)(20)(21)(22)(23)(24). Generally speaking, a learning curve is considered to have been overcome when the monitored outcome indicators reach a steady state (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether or not prefer teaching VATS lobectomies to senior trainees with or without experience in traditional open lobectomy has been matter of discussion in several papers (13)(14)(15). According to those papers, VATS lobectomy remains a safe procedure, even if performed despite limited experience in open lobectomy, and affirm that the previous surgical training has a minimal impact on operative and postoperative outcomes (surgery time, blood loss, conversion rate, chest tube duration, postoperative morbidity and mortality).…”
Section: Stepwise Approach To Vats Lobectomy and Standardization Of Tmentioning
confidence: 99%